1992
DOI: 10.1161/01.str.23.5.712
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of polymorphonuclear leukocyte adherence suppresses no-reflow after focal cerebral ischemia in baboons.

Abstract: Background and Purpose: While polymorphonuclear leukocytes may contribute to the "no-reflow" phenomenon after focal cardiac and skeletal muscle ischemia/reperfusion, their contribution to acute focal cerebral ischemia is unresolved. We have examined the role of polymorphonuclear leukocytes in microvascular perfusion defects after focal cerebral ischemia/reperfusion in a baboon model of reversible middle cerebral artery occlusion with the anti-CD18 monoclonal antibody IB4, which inhibits neutrophil adherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(185 citation statements)
references
References 46 publications
2
179
1
3
Order By: Relevance
“…A significant increase (p < 0.001) was seen postoperatively in total white cell count and absolute numbers of PMN leukocytes, followed by a return to baseline levels over 7 days. Baseline values for measurements ob tained from all subjects were in agreement with previously published values (Mori et al, 1992). No substantial changes in the platelet count were noted after the implantation procedure.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A significant increase (p < 0.001) was seen postoperatively in total white cell count and absolute numbers of PMN leukocytes, followed by a return to baseline levels over 7 days. Baseline values for measurements ob tained from all subjects were in agreement with previously published values (Mori et al, 1992). No substantial changes in the platelet count were noted after the implantation procedure.…”
Section: Resultssupporting
confidence: 89%
“…The surgical preparation of the nonhuman pri mate model for reversible MCA 0 involved implan tation of a Silas tic balloon occlusion device (Mentor Corporation and PS Medical, Goleta, CA, U.S.A.) through an orbital window (delZoppo et al, 1986) with the modifications noted by delZoppo et al, Mori et al, 1992). Following ketamine ana lepsis (10 mg/kg), anesthesia was routinely induced by inhalation of 3.0--5.0% halothane and maintained by halothane at 1.5-2.0%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, focal I/R induces recruitment and activation of inflammatory cells, which are thought to be key events causing I/R injury, represented by blood brain barrier (BBB) breakdown brain edema, neural death, and hemorrhagic transformation (Amantea et al, 2009;Jin et al, 2010). Many studies have shown that systemic suppression of neutrophils attenuated I/R injury in a transient middle cerebral artery occlusion (MCAO) model (Matsuo et al, 1994;Mori et al, 1992;Zhang RL et al, 1994;Connolly et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…18 The "no reflow" effect can be considerably reduced by the monoclonal antibody IB4, which inhibits neutrophil adhesion to the endothelium. 19 Red blood cell aggregation near the exit of capillaries pushes leukocytes against endothelial cells, thereby increasing leukocyte adhesion. 20 Leukocyte adhesion (and reperfusion damage) is higher in older animals.…”
Section: Blood Vesselsmentioning
confidence: 99%